Citalopram overdose: Late presentation of torsades de pointes (TdP) with cardiac arrest - Tarabar, Asim F. (Springer-Verlag, 2008)
INTRODUCTION: Citalopram overdose may produce bradycardia, QT prolongation, and torsades de pointes (TdP). A cardiotoxic metabolite may be responsible for the delayed onset of cardiotoxicity. Although some authorities recommend a minimum of 24 hours of observation following citalopram overdose, a recent analysis suggested that dysrhythmias rarely occur beyond 13 hours post-ingestion. We present a case of citalopram overdose with a substantially delayed onset of cardiac toxicity. CASE REPORT: A 36-year-old woman complained of shakiness, numbness in the arms, and palpitations that began approximately 32 hours after ingesting 50 (20-mg) tablets of citalopram. Her initial vital signs were: blood pressure, 84/44 mmHg; pulse, 102–150/minute; respirations, 17/min; temperature, 99.3° F (37.3° C). Her initial ECG showed sinus rhythm with a prolonged corrected QT interval (572 msec) with paroxysmal, self-limited runs of wide-complex tachycardia that appeared multifocal in nature. Approximately 20 minutes after presentation, she experienced self-terminating TdP, with transient hypotension and loss of consciousness. Her serum citalopram concentration (33 hours post-ingestion) was 477 ng/mL (therapeutic: 40–110 ng/mL); desmethylcitalopram concentration was 123.2 ng/mL (therapeutic: 14–40 ng/mL). She was treated with magnesium and lidocaine, and her corrected QT interval remained abnormal for 24 hours after presentation. DISCUSSION: Citalopram overdose can produce life-threatening cardiac toxicity with a clinical onset that may be delayed beyond a routine observation period of 6 hours. Once the QT interval is prolonged, it seems prudent to prolong the observation period.